Can serial focussed echocardiographic evaluation in life support (FEEL) predict resuscitation outcome or termination of resuscitation (TOR)? A pilot study. (April 2016) - Kim, Han Bit; Suh, Jun Young; Choi, Jae Hyung; Cho, Young Soon
Abstract: Aim of the study: This study aimed to evaluate the correlation between serial echocardiography findings and return of spontaneous circulation (ROSC) in patients with out-of-hospital cardiac arrest (OHCA) and to examine whether echocardiographic cardiac standstill duration can be used to predict ROSC. Methods: This was a prospective observational study of non-consecutive non-trauma adult patients with OHCA. Echocardiography was performed every 2 min during a pulse check for <10 s throughout the resuscitation effort managed according to advanced life support treatment guidelines. Echocardiography findings were recorded as video clips. Results: Forty-eight patients were enrolled in the study. Serial echocardiographic cardiac standstill duration in the ROSC and no ROSC groups were 2.86 ± 2.07 min versus 20.30 ± 8.42 min, respectively ( p < 0.001). Cardiac standstill duration ≥10 min predicted non-ROSC with a sensitivity of 90.0%, specificity of 100%, positive predictive value of 100%, and negative predictive value of 93.3%. A receiver operating characteristic curve was generated to determine the accuracy of serial echocardiographic cardiac standstill duration for predicting no ROSC. The area under the curve was 0.991 ( p < 0.000). Conclusions: In all patients with serial echocardiographic cardiac standstill ≥10 min, no patients had ROSC. These results displayed compelling test performance and discrimination ability for subjects with and without ROSC. Our study is suggestive, and it warrants further study.